Hush Now, Baby : A Memoir - Williams, Angela W., 1941- (Book collections on Project MUSE., 2015)
Hush Now, Baby is the story of how a little white girl climbed out of an uneasy childhood in the segregated South...on the backbone of a black woman who loved her unabashedly. A host of African-American women permeated Southern families. One of those stalwart women was Eva Aiken, a central figure in the author's life from her birth...until Eva staged a sit-in at the girl's wedding. The story captures the glorious early years of the Lowcountry South Carolina family then graphically depicts its unraveling. Eva holds them together. The family and the country's parallel struggles converge. The author lives in bubble-wrap until Civil Rights issues escalate. This story is told without pathos and with graceful restraint-the Southern way. "Angela's prose plunges us back in time when a generation of white children were raised by the calloused hands of slaves who, despite being freed by Lincoln, remained chained to a stubborn way of life. Instead of killing us in our sleep, they became our guardian angels, for reasons still mysteriously misunderstood." --Ken Burger, author of Swallow Savannah, Sister Santee, Salkehatchie Soup, and Baptized in Sweet Tea. --Provided by publisher.